Ethical recognition of the victims of market violence - Etxeberria, Xabier (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
This study takes on the challenge of applying the concept of philosophical recognition to the victims of market violence. The author discusses several dimensions of recognition, which are then projected onto the victims: Unfair suffering as an expression of misrecognition, the scheme of recognition and the victims that are generated when applied by the markets, the relevance of the institutional dimension and of identity in the victimizing market space, the struggle for recognition of/ with the victims, and its perspective of justice.